Ultrasound-guided versus palpation-guided platelet-rich plasma injection for the treatment of chronic lateral epicondylitis: A prospective, randomized study - Gonca Sağlam,; Dilek Çetinkaya Alişar, (Archives of Rheumatology, 2023)
Objectives: This study aims to compare the effectiveness of palpation-guided and ultrasound (US)-guided platelet-rich plasma (PRP) injections in patients with chronic lateral epicondylitis (LE). Patients and methods: Between January 2021 and August 2021, a total of 60 patients (34 males, 26 females; mean age: 40.5±10.9 years; range, 22 to 64 years) diagnosed with chronic LE were included. The patients were randomly allocated to either the palpation-guided (n=30) or the US-guided injection group (n=30) before they received PRP injection. All patients were assessed using the Visual Analog Scale (VAS), Disabilities of the Arm, Shoulder and Hand (DASH) scale, and grip strength at baseline and at one, three, and six months after injection. Results: Baseline sociodemographic and clinical variables were statistically similar between two groups (p>0.05). The VAS and DASH scores improved significantly after the injection at each control, as well as grip strength in both groups (p<0.001). No statistically significant difference was found between the groups regarding VAS and DASH scores, and grip strength at one, three, and six months post-injection (p>0.05). No significant complication related to the injection was observed in any of the groups. Conclusion: This study demonstrates that both palpation-guided and US-guided PRP injection protocols can improve clinical symptoms and functional parameters of patients with chronic LE.